Coprophilous Agaricales (Agaricomycetes, Basidiomycota) from Brazil - Melo, Roger Fagner Ribeiro; Chikowski, Renata Dos Santos; Miller, Andrew Nicholas; Maia, Leonor Costa (Phytotaxa, 2016)
During a survey of coprophilous fungi along a gradient through different vegetational areas in Pernambuco, northeastern Brazil, twelve species of dung inhabiting mushrooms were reported. Bolbitius demangei, Conocybe siliginea, Coprinellus angulatus, C. marculentus, Coprinopsis cothurnata, C. pseudoradiata, C. vermiculifer and Coprinus foetidellus are new records for Brazil. Descriptions and drawings are provided, along with an identification key to all Agaricales species recorded on dung in Brazil.